CEP164 is essential for efferent duct multiciliogenesis and male fertility. Issue 2 (8th July 2021) - Hoque, Mohammed; Chen, Danny; Hess, Rex A; Li, Feng-Qian; Takemaru, Ken-Ichi
Abstract : Cilia are evolutionarily conserved microtubule-based structures that perform diverse biological functions. Cilia are assembled on basal bodies and anchored to the plasma membrane via distal appendages. In the male reproductive tract, multicilia in efferent ducts (EDs) move in a whip-like motion to prevent sperm agglutination. Previously, we demonstrated that the distal appendage protein CEP164 recruits Chibby1 (Cby1) to basal bodies to facilitate basal body docking and ciliogenesis. Mice lacking CEP164 in multiciliated cells (MCCs) (FoxJ1-Cre;CEP164 fl/fl ) show a significant loss of multicilia in the trachea, oviduct, and ependyma. In addition, we observed male sterility; however, the precise role of CEP164 in male fertility remained unknown. Here, we report that the seminiferous tubules and rete testis of FoxJ1-Cre;CEP164 fl/fl mice exhibit substantial dilation, indicative of dysfunctional multicilia in the EDs. We found that multicilia were hardly detectable in the EDs of FoxJ1-Cre;CEP164 fl/fl mice although FoxJ1-positive immature cells were present. Sperm aggregation and agglutination were commonly noticeable in the lumen of the seminiferous tubules and EDs of FoxJ1-Cre;CEP164 fl/fl mice. In FoxJ1-Cre;CEP164 fl/fl mice, the apical localization of Cby1 and the transition zone marker NPHP1 was severely diminished, suggesting basal body docking defects. TEM analysis of EDs further confirmed basal body accumulation in the cytoplasm of MCCs. Collectively, we conclude that male infertility in FoxJ1-Cre;CEP164 fl/fl mice is caused by sperm agglutination and obstruction of EDs due to loss of multicilia. Our study, therefore, unravels an essential role of the distal appendage protein CEP164 in male fertility.